The suitability and practicality of the OECD transfer pricing methods to Zimbabwe - Ncube, Andile (Department of Finance and Tax, 2023)
The provisions of Section 98B of the Zimbabwe Income Tax Act as read with the 35th schedule governing all related party transactions both domestic and cross border between companies forms the foundation of the transfer pricing legislative regulatory framework in Zimbabwe. The arm's length principle (ALP) is the source of applying the provisions in the regulations. Reference to the Organisation of Economic Cooperation and Development (OECD) comprehensive transfer pricing guidelines is given for interpretation purposes. Although Zimbabwe is not a member of the OECD it adopted the transfer pricing guidelines. This study examines the Zimbabwe Transfer Pricing Legislation with the aim of establishing the suitability and practicality of the transfer pricing methods for Zimbabwe. The unique Zimbabwean economic situation is considered. As a taxation tool, the guidelines' suggested methods have been applied with a lot of challenges, sometimes resulting to unwarranted loss of revenue with comparability being the major source of difficulties. It is against this backdrop that it was found necessary to examine the level in which OECD methods are relevant and applicable in the Zimbabwe's tax regime. To achieve this, this study identifies the 5 OECD transfer pricing methods and the comparability challenges that are faced when applying them to establish the arm's length prices. Comparability is an intrinsic part of the application of the Arm's Length Principle, which requires comparison of conditions under which related enterprises transact compared to those entered by unrelated enterprises (McNair, 2012). “The issue of comparability remains the cornerstone of transfer pricing” (Sikka, P. and Willmott, H., 2010). The comparability analysis should result in a range of prices, set for uncontrolled transactions with conditions like those of the controlled transactions (McNair, 2012). The five existing comparability factors are (i) the characteristics of the property or services transferred, (ii) the functions performed considering the assets used and risks assumed, (iii) the contractual terms, (iv) the economic circumstances of the parties and (v) the business strategies pursued by the parties (OECD, 2017). Overall the ALP, applied through specific pricing methodologies evaluated in this dissertation, is considered to provide a reasonable arm's length price. The applicability the methods is however, specific to each transaction and the accessibility of comparable information. Inadequate information on comparable uncontrolled transactions in Zimbabwe makes the application of the arm's length principle cumbersome. v ANDILE NCUBE NCBAND004 - The suitability and practicality of the OECD Transfer Pricing Methods to Zimbabwe Moreover, other general problems include the size of the market being considered which limits the nature and extent of information available; the time and expense involved in undertaking comparability analyses; and underestimation of the impact of the differences between the tested party and the comparables (Ado, E. 2015). These problems can be a hindrance in achieving the desired level of comparability and, therefore, can affect the accurate application of the arm' s length principle. Hence it is necessary to consider other options to ensure certainty and to avoid the adverse effects of double taxation and double non-taxation that may otherwise arise. Further, the research showed that Zimbabwe is lagging as there is no compliance threshold for documentation, no practice notes for guidance, and does not subscribe to the BEPS Action plan. The three main risks that were identified included the following the following: ➢ Unavailability of a database that will assist the revenue authorities in determining an appropriate arm's length price. ➢The inadequacy of skills, know-how and experience in evaluating arm's length prices. ➢ The challenges of having access to relevant, appropriate, and apt information to precisely determine arm's length price for different classes of transactions. In Zimbabwe, both the economic and political climate has been volatile over years, as result comparable transactions are less existent. For example, the period 1998-2007 was the Zimbabwe Dollar era, 2008 was hyper-inflationary period, 2009-2013 the economy and trade improved, and the period 2014-2018 has been a fall in economy activities and changes to the political landscape. All these trends affect the availability of comparable transactions. For this reason, it is very important for the taxpayer to critically assess the acceptability of the comparable data chosen, consider and document any adjustments and ensure that an adequate comparability analysis, including the review of more than one transfer pricing methodology, has been performed and recorded in full (Miller, K. and Joubert, B., 2016). Lastly, appropriate recommendations are then made to the relevant authorities for a possible modification and or provide guidance with regards to the Transfer Pricing legislation.